Access or Ownership? The effect of car attributes and collective psychological ownership on the preference for car subscription services - Szamatowicz, Marcin; Paundra, Joshua (UI Scholars Hub, 2019)
Alternative transportation services for urban commuters expand with car subscription services. Car subscription services give drivers access to cars without ownership for a relatively longer time period (e.g., months) than other sharing economy transportation services. Based on a mix of between- and within-subject design online experiment involving 274 participants, this study investigates traditional and upcoming subscribed car features namely, mileage limit, price, self- driving capability, advanced safety systems, and the moderating influence of collective psychological ownership of these features on people’s preference for car subscription services. The results suggest that these features significantly impact people’s preference toward this service. Collective psychological ownership was found to moderate the influence of self-driving capability and advance safety systems on people’s preference for car subscription services. Individuals with high collective psychological ownership preferred subscription cars with self-driving capability and were more concerned with the lack of advanced safety systems in a subscription car. Car subscription companies need to consider traditional (price and mileage limit), and upcoming features (self-driving capability and advance safety systems) when offering their services. More importantly, the moderating influence of collective psychological ownership on these features means that car subscription companies should account for people’s psychological disposition when considering additional car features.